Coronary artery mycotic aneurysm in a patient suffering from subacute endocarditis: a case report and literature review - Hali, Reza; Sharifkazemi, Mohammadbagher; Yaminisharif, Ahmad; Bagheri, Jamshid; Shahbazi, Narges (Frontiers in Cardiovascular Medicine, 2023)
Although mycotic aneurysm is a known and important disease in the cerebrovascular system, especially the brain, there are scarce reports about coronary artery mycotic aneurysms (CAMA). CAMA can occur not only in the context of endocarditis but also as a rare adverse event of coronary artery stenting, which has been used more extensively in recent years. Accordingly, it is essential to pay greater attention to its associated presentations and clinical course. Considering the scant evidence available, reporting the disease course of each patient with CAMA can help increase the physician’s knowledge about this condition, which is why we are reporting this case. A 42-year-old man with diabetes was referred to our center with embolic left cerebellar infarction 3 months earlier, as well as a 2-month history of feverishness before his referral. His blood culture was positive for Viridans Streptococci, and he had paraclinical signs of inflammation and two- and three-dimensional transthoracic and transesophageal echocardiography (2D & 3D TTE and TEE) signs of aortic and mitral valves’ infective endocarditis with the destruction of the aortic valve, severe aortic and mitral regurgitation, severe pulmonary hypertension, and moderate biventricular systolic dysfunction. Regarding the obviously dilated left main coronary artery on TEE images, contrast-enhanced chest multidetector computed tomography was performed for better assessment of coronary arteries with suspicion of CAMA, which confirmed aneurysmal dilatation of the proximal left main coronary artery. The presence of bacteria was confirmed on staining the valvular tissue, resected during the surgical replacement of aortic and mitral valves. As the cardiac surgeon considered CAMA resection and coronary bypass grafting high risk for the patient, he received parenteral antibiotic therapy, for 6 weeks. At 1-year follow-up, he was doing well with no signs/symptoms of endocarditis and well-functioning mechanical prosthetic valves. This case shows the significance of considering CAMA in the setting of endocarditis, resistant to medical and/or surgical therapy or in patients with coronary aneurysm, simultaneous with active endocarditis. Therefore, more attention should be paid to this extravalvular complication of endocarditis, and its possibility should be considered and investigated in any patient presented with valvular endocarditis, especially involving the aortic valve.